Recent Advances in Epsilon-Poly-L-Lysine and L-Lysine-Based Dendrimer Synthesis, Modification, and Biomedical Applications - Chen, Sijin; Huang, Shuting; Li, Yan; Zhou, Chuncai (Frontiers in Chemistry, 2021)
With the advantages in biocompatibility, antimicrobial ability, and comparative facile synthesis technology, poly-L-lysine (PLL) has received considerable attention in recent years. Different arrangement forms and structures of the backbone endow lysine-based polymers with versatile applications, especially for EPL and LBD compounds. This review summarized the advanced development of the synthesis and modification strategies of EPL and LBD, focus on the modification of bio-synthesis and artificial synthesis, respectively. Meanwhile, biomedical fields, where EPL and LBD are mainly utilized, such as agents, adjuvants, or carriers to anti-pathogen or used in tumor or gene therapies, are also introduced. With the deeper of knowledge of pharmacodynamics and pharmacokinetics of the drug system, the design and synthesis of these drugs can be further optimized. Furthermore, the performances of combination with other advanced methodologies and technologies demonstrated that challenges, such as scale production and high expenses, will not hinder the prospective future of lysine-based polymers.